0802 To Examine the Effect of Gabapentin Enacarbil in Primary Restless Legs Syndrome Patients Who are on Dopaminergic Agents and Exhibiting Augmentation. (27th May 2020) - Bollu, P; Goyal, M; Sivaraman, M; Taylor, N; Yin, L; Thakkar, M; Sahota, P
Abstract: Introduction: Augmentation is defined as worsening of the symptoms of Restless Legs Syndrome after a brief period of initial improvement with dopaminergic agents resulting in either an earlier onset, increase in severity, quicker onset, spread to other body parts. The exact prevalence of this phenomenon is not known and in patients experiencing augmentation, it can pose a difficult diagnostic and therapeutic challenge to the clinician. In our study, we found extended-release gabapentin to be an effective intervention in patients experiencing dopaminergic augmentation Methods: This is an open-label single-arm study done in patients exhibiting augmentation while on dopaminergic agents. Patients who were enrolled in the study were initiated on oral extended-release gabapentin(Horizont) 600 mg at 5 pm at the beginning of the study. At day 90, attempts were made to reduce or discontinue dopaminergic agents. International Restless Legs Syndrome-Rating Scale (IRLS) and Augmentation Severity Rating Scale(ASRS) were recorded at each visit. Results: A total of 10 patients were enrolled in the study while only 8 patients completed it. Compared to the baseline (visit 2), there is a significant improvement in both the augmentation severity(p= 0.0131) and the IRLS (p=0.0497). Wilcoxon matched-pairs signed rank test was used for statistical analysis. Conclusion: Extended-release Gabapentin is an effective treatment option in primary RLS patients experiencing augmentation secondary to dopaminergic medication usage. Support: The study is funded and medication is provided by Arbor Pharmaceuticals.